Penetration depth study of A Nd: YAG laser welding on aluminium /cAhmad Farhan Fadzlu-llah - 492596 Ahmad Farhan Fadzlu-llah; Jalil Ali, supervisor; Fakulti Sains
Project Paper (Sarjana Muda Sains (Fizik)) - Universiti Teknologi Malaysia, 2010